Phenotypic variability in deficiency of the α subunit of succinate‐CoA ligase. Issue 1 (14th March 2019) - Demirbas, Didem; Harris, David J.; Arn, Pamela H.; Huang, Xiaoping; Waisbren, Susan E.; Anselm, Irina; Lerner‐Ellis, Jordan P.; Wong, Lee‐Jun; Levy, Harvey L.; Berry, Gerard T.
Abstract: Succinyl‐CoA synthetase or succinate‐CoA ligase deficiency can result from biallelic mutations in SUCLG1 gene that encodes for the alpha subunit of the succinyl‐CoA synthetase. Mutations in this gene were initially associated with fatal infantile lactic acidosis. We describe an individual with a novel biallelic pathogenic mutation in SUCLG1 with a less severe phenotype dominated by behavioral problems. The mutation was identified to be c.512A>G corresponding to a p.Asn171Ser change in the protein. The liquid chromatography tandem mass spectrometry‐based enzyme activity assay on cultured fibroblasts revealed a markedly reduced activity of succinyl‐CoA synthetase enzyme when both ATP and GTP were substrates, affecting both ADP‐forming and GDP‐forming functions of the enzyme.